Extreme-Value Statistics for Testing Dark Energy. Issue Volume 10:Issue S306(2014) (1st July 2015) - Aiola, Simone; Kosowsky, Arthur; Wang, Bingjie
Abstract: The integrated Sachs-Wolfe effect was recently detected at a level of 4.4σ by [Granett et al. (2008 )], by stacking compensated CMB temperature patches corresponding to superstructures in the universe. We test the reported signal using realistic gaussian random realizations of the CMB sky, based on the temperature power spectrum predicted by the concordance ΛCDM model. Such simulations provide a complementary approach to the largely used N-body simulations and allow to include the contaminant effects due to small-scale temperature fluctuations. We also apply our pipeline to foreground-cleaned CMB sky maps using the [Granett et al. (2008 )] voids/clusters catalog. We confirm the detection of a signal, which depart from the null hypothesis by 3.5σ, and we report a tension with our theoretical estimates at a significance of about 2.5σ.